Kompressi Citra Diam Secara Adaptif:Pemilih Pohon Basis Cosine Packets(CP) Dan wavelet Packets(WP) menggunakan Algoritma Pruning Optimal - Perpustakaan UGM, i-lib ([Yogyakarta] : Fakultas MIPA Universitas Gadjah Mada, 2004)
ABSTRAK Both wavelet packets (WP) and cosine packets (CP) have recently emerged as powerful tools for signal compression, particularly in areas of still image and video compression. This is a comparative study of performance on transform based coding image compression algorithms. The entropy-based criterion and optimal pruning algorithm are used to choose the best decomposition tree of CP and WP. To obtain a quantitative measure of our methods's performance, we give PSNR (peak signal to noise ratio), time-consumption and sum of zeros percentage parameters. The sum of zeros percentage parameter showed that WP will be the winner if the decomposition level is 5 and 6. Otherwise CP will be the winner if the decomposition level is 1 . This indicates WP is better than CP regarding to energy compaction. Other parameters proved that WP is better than CP. Keywords: wavelet packets (WP), cosine packets (CP), PSNR, time-consumption, sum of zeros percentage.